The Concept of Salvation in the Qur'an: A Theological Analysis and Comparative Study with Other Abrahamic Traditions - Ichwan, Moh. Nor; Nabavi, Sayed Majid; Benaouali, Mohamed Cherif (International Journal of Religious and Interdisciplinary Studies, 2025)
The concept of salvation is a crucial theological issue debated within Islam, Christianity, and Judaism Abrahamic traditions. While these three religions share similarities in emphasizing faith and ethical behavior, they exhibit fundamental differences regarding the mechanisms of salvation. This study highlights that Islam emphasizes a balance between divine grace and individual responsibility, contrasting with Christianity's focus on grace and redemption through Jesus Christ and Judaism's emphasis on obedience to God's covenants and laws. Utilizing a qualitative approach, the research employs textual analysis of the holy scriptures from each tradition alongside comparative theological studies. The findings reveal that the Qur'an integrates divine grace (rahmah) and human effort (amal salih), presenting a holistic view of salvation that differs from the grace-centered model of Christianity and the law-centered approach of Judaism. This study contributes to a deeper understanding of soteriology across these traditions and fosters constructive interreligious dialogue by illuminating both shared values and distinct theological perspectives.